EU civilian crisis management : the record so far - Chivvis, Christopher S.; Rand eBooks (Santa Monica, CA : RAND, 2010)
The European Union has been deploying civilians in conflict and postconflict stabilization missions since 2003, and the scope of civilian missions is likely to increase in the future. This volume offers a general overview and assessment of the EU's civilian operations to date, as well as a more in-depth look at the two missions in which the EU has worked alongside NATO: the EU police-training mission in Afghanistan and the integrated rule of law mission in Kosovo. The author concludes with a discussion of the main policy implications for the United States and Europe.
Introduction -- The European Union's Civilian-Military Capabilities -- EUPOL Afghanistan -- EULEX Kosovo -- Conclusions.
"RAND National Defense Research Institute."
Includes bibliographical references (p. 49-52).
Also available on the internet via WWW in PDF format.
Keywords: North Atlantic Treaty Organization; Civil-military relations -- European Union countries; Crisis management -- European Union countries; European Union countries -- Military policy; Military missions; Postwar reconstruction -- Afghanistan; Postwar reconstruction -- Kosovo (Republic).; Electronic books